EU mapping: Systematic overview on economic and financial legislation - Marcel Gellings; Kai Jungbluth; Katja Langenbucher (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
In this study prepared for the ECON Committee of the European Parliament, Gellings, Jungbluth and Langenbucher present a graphic overview on core legislation in the area of economic and financial services in Europe. The mapping overview can serve as background for further deliberations. The study covers legislation in force, proposals and other relevant provisions in fourteen policy areas, i.e. banking, securities markets and investment firms, market infrastructure, insurance and occupational pensions, payment services, consumer protection in financial services, the European System of Financial Supervision, European Monetary Union, Euro bills and Coins and statistics, competition, taxation, commerce and company law, accounting and auditing.
urn:nbn:de:hebis:30:3-344470
Keywords: 330; EU economic and financial services legislation